Samson and Delilah: a close-up of Aboriginality in the contemporary moment - Polak, Iva (2010)
The paper focuses on the critically acclaimed film Samson and Delilah (2009) by Aboriginal director Warwick Thornton. The film exposes the white ideological frame and paternalistic assumptions about acceptable representations of Aboriginality testifying to the famous claim by Graeme Turner that cinematic representations of Aboriginality by non-Indigenous directors cannot be achieved by simple inversion of conventional narrative structures or by mere focusing on Aboriginal characters. Hence, Samson and Delilah subverts an overwhelming number of non-Indigenous cinematic representations of Aboriginality by laying bare hard-boiled images of Aboriginality in the contemporary Australian moment, which are presented on the screen in an easygoing manner. Thornton’s film is also in contrast to the most recent Aboriginal films which are more ludic in tone, such as Stone Bros (2009) by dir. Richard Frankland, and Bran Nue Dae (2010) by dir. Rachel Perkins, and stays in tune with Ivan Sen’s Beneath Clouds (2002) by unwrapping a story in slow motion, about a mock-biblical teenage couple living on the margins of the already marginalized society. Set in the barren landscape of the mythopoetic heart of Australia, Thornton’s film shows what it means to lose heart and take heart in a space where policies of “globalization”, “multiculturalism”, “reconciliation”, and the “official apology” are as remote as the location itself.
Projekt MZOS
ENG